Routes to Writing in Southern Africa: By Brenda Leibowitz and Yasien Mohamed. (Cape Town, South Africa: Silk Road International Publishers, 2001. p. 285. ISBN 1-875047-050) (American Journal of Islam and Society, 2001)
Writing is certainly one of man's greatest inventions, and good writing is askill which elevates one's position in the society of the learned. The otherside of the coin is poor writing that leads to poor communication and oftenmiscommunication between the writer and the reader(s). Writing in theacademic world is all the more important, as it is the only means ofscholarly expression. The quality of good writing skills is a cause ofconcern for many teachers at various stages of education, especially at thetertiary level. This is perhaps more true of students whose native languageis not English, and for lecturers who have to teach such students.The book under review is a collection of essays written by lecturers andwriting specialists primarily at the University of Western Cape (UWC).It is divided into six major parts and fourteen chapters. The essays arewritten on various themes that provide guidelines for developing writingskiUs in the academic setting. The book is edited by Brenda Leibowitz,Director of the National Center for Curriculum Research and Developmentat the Department of Education, and Yasien Mohamed, a senior lecturer inthe Department of Foreign Languages at UWC.The editors have compiled this book with the aim of providing insight,reflection, and guidelines that would empower lecturers to teach theirsubject more effectively and especially to help students with the writingaspect of their university study. Mohamed, who wrote the introduction tothe book, comments that writing and its development should be viewed asa "humanistic" activity, which recognizes the natural and creative forms ofpersonal narrative writing, as opposed to a scientific approach, wherewriting is viewed as a product rather than a process. Actually, thisempathetic approach to writing development is evident lhroughout thebook.Part I of the book consists of one chapter only and deals with theimportance of writing and teaching in the academia, emphasizing the needfor lecturers to be evaluative of their own writing practices. Basing theadvice on many years of experience as a trainer of writing, the authorsuggests many useful writing strategies including the use of dialogicmaterials, mind mapping, free writing, and writer's support groups.Part II deals with diversity, culture, and writing, and consists of chapters ...